Corpus linguistics on the move : exploring and understanding English through corpora - López-Couso, María José; Méndez-Naya, Beléna; Núñez Pertejo, Paloma; Palacios Martínez, Ignacio M. (Ignacio Miguel), 1959- (Language and computers, 2016)
Corpus linguistics on the move: Exploring and understanding English through corpora' comprises fourteen contributions by leading scholars in the field of English corpus linguistics, covering areas of central concern in corpus research and corpus methodology. The topics examined in the different chapters include issues related to corpus compilation and annotation, perspectives from specialized corpora, and studies on grammatical and pragmatic aspects of English, all these examined through a broad range of corpora, both synchronic and diachronic, representing both EFL and different native varieties of English worldwide. The volume will be of primary interest to students and researchers working on English corpus linguistics, but is also likely to have a wider general appeal.